SIRT1 prevents noise-induced hearing loss by enhancing cochlear mitochondrial function - Yuelian Luo; Haoyang Wu; Xin Min; Yi Chen; Wenting Deng; Minjun Chen; Chuxuan Yang; Hao Xiong (Cell Communication and Signaling)
Abstract Exposure to traumatic noise triggers cochlear damage and consequently causes permanent sensorineural hearing loss. However, effective treatment strategies for noise-induced hearing loss (NIHL) are lacking. Sirtuin 1 (SIRT1) is a NAD+-dependent deacetylase that plays a critical role in multiple physiological and pathological events. However, its role in NIHL pathogenesis remains elusive. This study revealed that SIRT1 expression in the cochlea progressively decreases in a mouse model of NIHL. Hair cell-specific knockout of SIRT1 exacerbates the noise-induced loss of outer and inner hair cell synaptic ribbons, retraction of cochlear nerve terminals, and oxidative stress, leading to more severe NIHL. Conversely, adeno-associated virus (AAV)-mediated SIRT1 overexpression effectively attenuated most noise-induced cochlear damage and alleviated NIHL. Transcriptomic analysis revealed that SIRT1 deficiency impairs glucose metabolism and inhibits antioxidant pathways in the cochlea following exposure to noise. Further investigation revealed that SIRT1 exerts an antioxidant effect, at least in part, through AMPK activation in cultured auditory HEI-OC1 cells exposed to oxidative stress. Collectively, these findings indicate that SIRT1 is essential for the maintenance of redox balance and mitochondrial function in the cochlea after traumatic noise exposure, thus providing a promising therapeutic target for NIHL treatment. Graphical Abstract Schematic illustration of SIRT1’s protective role and mechanism in NIHL. Exposure to noise leads to downregulation of SIRT1 and phosphorylated AMPK (p-AMPK) levels, which subsequently triggers OHC loss, synaptopathy, and neurite retraction in the cochlea. This cascade results in mitochondrial dysfunction, which is characterized by reduced ATP production and increased ROS accumulation, with a concomitant decrease in antioxidant capacity. To counteract these adverse effects, AAV-mediated SIRT1 overexpression (AAV-SIRT1) has been explored as a therapeutic strategy to restore SIRT1 levels and protect against NIHL.